Machado de Assis e a (re)escrita de Oliver Twist - Camelo, Franciano (2013)
In early 1870, Machado de Assis translated part of Oliver Twist, a novel by Charles Dickens (LÍSIAS, 2002). Although unfinished, since the Brazilian writer stopped his contribution at chapter twenty-eight, this translation presents particularities, which are worth being analysed. It is especially noticeable the French mediation in the translation of the Dickensian novel into Portuguese as well as the manipulation of the narrative, which remodelled the novel (MASSA, 1965). Recent studies approached the issue to a limited extent, mainly for not regarding the implications of both major and minor adjustments promoted by Machado. Hence, this study has a two-fold purpose: a) to investigate the route of Oliver Twist to Brazil, through the analysis of the relation between the English editions of this novel, the French translation made by Alfred Gérardin and the Brazilian translation by Machado de Assis; b) to analyse in detail the procedures adopted by the Brazilian writer while translating Dickens novel and discuss their implications for the narrative structure. The (re)writing of Oliver Twist seems to have encompassed, so as to say, a process of selection of repertoire and formal reorganisation of the narrative, which appears to respond to the specificity of nineteenth-century Brazilian context of reception.